Macroeconomic determinants of corporate failures in Malaysia - Ahmad, Abd Halim @ Hamilton; Mohd Daud, Siti Nurazira; Mazlan, Ahmad Rizal; Marzuki, Ainulashikin (Canadian Center of Science and Education, 2008)
This research investigates the long-run dynamic linkages between the corporate failures in Malaysia and selected macroeconomic variables by employing the Autoregressive Distributed Lag (ARDL) bound test, a robust and recent time series technique which is applicable irrespective of whether the regressors are I(0) or I(1).Corporate failure rate is the ex-ante variable in a linear function model with five explanatory macroeconomic variables. A dummy variable to decipher the corporate failure rates during the Asian financial crisis was also included. The results show that corporate failure rates in Malaysia are significantly and positively associated with the average lending rate, inflation rate and, gross domestic product (GDP) in the long-run.